2016
DOI: 10.1186/s40885-016-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive crisis in children: an experience in a single tertiary care center in Korea

Abstract: BackgroundHypertensive crisis is a medical emergency that can cause acute damage to multiple end-organs. However, relatively little is known on the etiology, treatment, and outcomes of hypertensive crisis in Korean children. The aim of this study was to determine the etiologies and efficacy of drugs for hypertensive crisis in children during the past 5 years at a single center in Korea.MethodsWe analyzed data from 51 children with hypertensive crisis during the period between January 1, 2010 and April 1, 2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
(19 reference statements)
2
12
1
5
Order By: Relevance
“…All patients presenting with hypertensive crisis do warrant a thorough evaluation to look for an underlying secondary cause for hypertension as directed by their clinical symptoms, presentation, and examination findings. A retrospective cohort study, looking at the etiology, treatment, and outcomes of the pediatric hypertensive crisis amongst pediatric patients presenting to Yonsei University Severance Hospital, South Korea, was performed by Lee et al 1 In this study, all 51 patients received treatment with either labetalol, hydralazine, nicardipine or nitroprusside. In contrast, only 34 (72.3%) of our patients received antihypertensive medications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients presenting with hypertensive crisis do warrant a thorough evaluation to look for an underlying secondary cause for hypertension as directed by their clinical symptoms, presentation, and examination findings. A retrospective cohort study, looking at the etiology, treatment, and outcomes of the pediatric hypertensive crisis amongst pediatric patients presenting to Yonsei University Severance Hospital, South Korea, was performed by Lee et al 1 In this study, all 51 patients received treatment with either labetalol, hydralazine, nicardipine or nitroprusside. In contrast, only 34 (72.3%) of our patients received antihypertensive medications.…”
Section: Discussionmentioning
confidence: 99%
“…Most children who present with hypertensive crisis have secondary hypertension 1,2 and renal pathology is the most common etiology. 2 To date, there remains limited data and consensus for the optimal treatment of hypertension in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the known presentations of hypertensive emergencies, acute neurological signs are most common and are a result of disruption of the blood-brain barrier, insufficient oxygen delivery, and edema and microhemorrhages (42). These neurologic symptoms may be non-specific, with 55% of patients experiencing headaches, 46% with dizziness, and 36% with nausea/vomiting, as in hypertensive urgency, but can also present with further signs of neurologic damage, with 16% presenting with altered consciousness and 11-20% experiencing seizures (16,43). A severe neurological complication of hypertensive crisis in children is posterior reversible encephalopathy syndrome (PRES), which principally involves damage to the occipito-parietal white matter and may spread to the basal ganglia, cerebellum, and brainstem.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Furthermore, hypertensive emergencies can cause cardiovascular remodeling in the form of left ventricular hypertrophy (LVH), which can consequently lead to congestive heart failure (CHF), manifesting with signs and symptoms such as dyspnea, chest discomfort, and gallop rhythm on auscultation. Several studies have shown that 13-26% of patients with hypertensive emergency have LVH (18,43). Of note, several case reports have shown that hypertensive crisis in infants and neonates may paradoxically present with hypotension and cardiogenic shock (48,49).…”
Section: Clinical Featuresmentioning
confidence: 99%